Vaccine hesitancy of Filipinos during the COVID-19 pandemic - De Leon, Naomi Diaz (Animo Repository, 2021)
One hindrance to the world's recovery from the devastating effects of the COVID 19 pandemic is vaccine hesitancy, or people's rejection of refusal to receive vaccines for the coronavirus. (Dror, 2020). Following the study of Taylor (2020), Perceived Vulnerability to Disease, Conspiracy Thinking, and Psychological Reactance were studied as predictors of Vaccine Hesitancy. Religiosity was also added as a fourth predictor given the religious context of the Philippines. The Health Belief Model was also used to analyze the predictors in their relationship to Vaccine Hesitancy. Through online convenience sampling, the researchers gathered 201 individuals, ranging from 18 to 65 years of age. To measure the 5 variables of the study, 5 different tests were used and were formatted into a Google Forms document. These tests were the Self-Report Scale to Measure “Perceived Vulnerability to Disease”, Generic Conspiracist Beliefs Scale for conspiracy thinking, Hong Psychological Reactance Scale, Religious Involvement Scale (RIS), and the Vaccine Hesitancy Survey (VHS). Multiple linear regression was conducted to determine the individual and total effects of the predictors toward Vaccine Hesitancy. Ethical considerations included prompting the respondent to have feelings of discomfort or trauma, as the study may revive the subjective negative experiences of the individual during the pandemic. Results showed that all predictors are significant, however, Perceived Vulnerability had an indirect relationship to vaccine hesitancy. The study suggests that for the Philippines to combat Vaccine hesitancy, conspiracy theories should be mitigated, vaccination programs should be non - coercive, religions should promote values that demote vaccine hesitancy, and Filipinos should be reminded that they are vulnerable to Covid - 19 if they are not vaccinated.